2018 ACC/HRS/NASCI/SCAI/SCCT Expert Consensus Document on Optimal Use of Ionizing Radiation in Cardiovascular Imaging—Best Practices for Safety and Effectiveness, Part 2: Radiological Equipment Operation, Dose‐Sparing Methodologies, Patient and Medical Personnel Protection. Issue 2 (29th August 2018) - ,; Hirshfeld, John W.; Ferrari, Victor A.; Bengel, Frank M.; Bergersen, Lisa; Chambers, Charles E.; Einstein, Andrew J.; Eisenberg, Mark J.; Fogel, Mark A.; Gerber, Thomas C.; Haines, David E.; Laskey, Warren K.; et al.
Abstract: The stimulus to create this document was the recognition that ionizing radiation‐guided cardiovascular procedures are being performed with increasing frequency, leading to greater patient radiation exposure and, potentially, to greater exposure to clinical personnel. While the clinical benefit of these procedures is substantial, there is concern about the implications of medical radiation exposure. ACC leadership concluded that it is important to provide practitioners with an educational resource that assembles and interprets the current radiation knowledge base relevant to cardiovascular procedures. By applying this knowledge base, cardiovascular practitioners will be able to select procedures optimally, and minimize radiation exposure to patients and to clinical personnel. "Optimal Use of Ionizing Radiation in Cardiovascular Imaging ‐ Best Practices for Safety and Effectiveness" is a comprehensive overview of ionizing radiation use in cardiovascular procedures and is published online. To provide the most value to our members, we divided the print version of this document into 2 focused parts. "Part I: Radiation Physics and Radiation Biology" addresses radiation physics, dosimetry and detrimental biologic effects. "Part II: Radiologic Equipment Operation, Dose‐Sparing Methodologies, Patient and Medical Personnel Protection" covers the basics of operation and radiation delivery for the 3 cardiovascular imaging modalities (x‐ray fluoroscopy, x‐ray computed tomography, and nuclear scintigraphy). For each modality, it includes the determinants of radiation exposure and techniques to minimize exposure to both patients and to medical personnel.